2007
DOI: 10.1002/jmri.20850
|View full text |Cite
|
Sign up to set email alerts
|

The magic angle effect: A source of artifact, determinant of image contrast, and technique for imaging

Abstract: This review provides a formalism for understanding magic angle effects in clinical studies. It involves consideration of the fiber-to-field angle for linear structures such as tendons, ligaments, and peripheral nerves, disc-like and circular structures such as menisci and labra, as well as complex three-dimensional structures. There may be one or more fiber types with different orientations within each of these tissues. The orientation of these fibers to B 0 is crucial in determining their magic angle effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
124
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 29 publications
4
124
0
3
Order By: Relevance
“…Their study demonstrated a good correlation between T 2 values using GRASE and TSE. Interestingly, since the GRASE sequence includes refocusing pulses (22), readings and measurements are similar to T 2 relaxation. Additionally, their study also lacks histological validation and is a limiting factor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Their study demonstrated a good correlation between T 2 values using GRASE and TSE. Interestingly, since the GRASE sequence includes refocusing pulses (22), readings and measurements are similar to T 2 relaxation. Additionally, their study also lacks histological validation and is a limiting factor.…”
Section: Discussionmentioning
confidence: 98%
“…It does have its own limitations such as sensitivity to susceptibility artifacts that are pronounced at the bone-cartilage interface or foreign body particles such postsurgical debris or metallic particles that may make accurate evaluation of cartilage difficult. Furthermore, the alpha-angle effect of increasing T 2 /T * 2 at an angle of ϳ55°to the main magnetic field has to be considered and monitored closely, especially in a spherically-shaped joint as the hip (22). The differences between the dGEMRIC and T* 2 technique regarding the interpretation of normal-appearing cartilage needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The MA is associated with a hyperintense T2 signal-intensity alteration in tissues densely composed of collagen, was first observed in tendons and ligaments, and was later reported also to occur in peripheral nerves. [9][10][11][12] It is conceived as a T2 signal-intensity increase related to the suppression of dipole-dipole interactions of the hydrogen protons bound to quasicrystalline structures such as tropocollagen, the triple-helical main compound of various types of fibrillary collagen. 13 The dipole-dipole interaction be-tween the highly ordered protons produces local magnetic fields with a field strength in the z-direction:…”
mentioning
confidence: 99%
“…The variance of ligament SI of the AOL and POL in our study compared to the reported low SI of ligaments might be related to the magic angle effect, as the echo times of the coronal and sagittal intermediated-balanced FS sequences were of 25 and 24 ms, respectively. Because of the horizontal orientation of the IML, the mostly striated appearance does not assume to be related to the magic angle effect, and instead might be due to the ligament morphology [30,31].…”
Section: Discussionmentioning
confidence: 99%